Preparation method of ceramic coated polyolefin diaphragm
By using a double-layer coating technology of porous epoxy adhesive and inorganic ceramic particles on the lithium battery separator, the problem of heat shrinkage of the lithium battery separator at high temperature is solved, and the permeability, adhesion and thermal resistance of the separator are improved.
Patent Information
- Application Number
- CN202411971634.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The existing lithium battery separators are easily heat-shrinkable at high temperatures, resulting in contact with the positive and negative electrodes and short-circuiting the battery. The bonding force between the ceramic particles and the polyolefin base film is weak, affecting the stability and permeability of the separator.
Porous epoxy adhesive is used as the inner layer slurry to form a first coating layer with excellent penetration as a buffer layer between the ceramic particles and the base film; the outer layer is made of inorganic ceramic particles and polyurethane adhesive to form a second coating layer, which improves the adhesion of the ceramic particles and reduces shrinkage stress.
The permeability and adhesion of the ceramic composite polyolefin separator is improved, the influence of heat shrinkage and shrinkage stress at high temperatures is reduced, and the thermal resistance and stability of the separator are enhanced.
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium batteries, and in particular to a method for preparing a ceramic-coated polyolefin diaphragm. Background Art
[0002] Lithium battery separator is the inner component used to separate the alternating positive and negative electrodes in lithium batteries. The separator is not conductive, but has the property of allowing electrolyte ions to pass through. Common lithium battery separators are made of polyolefin materials that are cheap, easy to process, and highly solvent-resistant; but due to the low softening and melting points of polyolefins (PE, PP), the separator is easily heated and contracted when the battery is heated, resulting in direct contact between the positive and negative electrodes and a short circuit in the battery, which is dangerous.
[0003] In order to improve the temperature resistance of lithium battery separators, without changing the base film material, researchers coated inorganic ceramic particles on the surface of the polyolefin base film, which greatly improved the separator's resistance to heat shrinkage, thermal rupture and puncture. The inorganic ceramic material itself has poor bonding with the polyolefin base film, so a certain volume of adhesive is required to bond it together. Although the porosity of the ceramic particle aggregates themselves is higher than that of the base film, it is easy to clog the micropores on the surface of the base film at the interface between the two, affecting the ion migration efficiency of the separator.
[0004] In addition, in many existing ceramic composite polyolefin diaphragms, the bonding force between ceramic particles and the base film is weak, so other technical solutions use strong adhesives such as polyurethane and acrylate for adhesion. However, the curing shrinkage rate of such resin-based adhesives is often large, and after curing, shrinkage stress will be generated on the surface of the polyolefin base film, and even tiny wrinkles will be generated, affecting the mechanical properties and stability of the diaphragm. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a ceramic composite polyolefin diaphragm with high permeability at an average porosity, in which the ceramic particles in the obtained ceramic composite polyolefin diaphragm have strong adhesion to the base membrane and have no obvious shrinkage stress effect on the base membrane surface.
[0006] The present invention provides a method for preparing a ceramic-coated polyolefin diaphragm, comprising the following steps:
[0007] The inner layer slurry is uniformly coated on at least one surface of the polyolefin base film, and a first coating layer is formed after solidification, cleaning and drying; the outer layer slurry is uniformly coated on the surface of the first coating layer, and a second coating layer is formed after solidification to obtain the ceramic coated polyolefin diaphragm;
[0008] The inner layer slurry includes porous epoxy adhesive, and the outer layer slurry includes inorganic ceramic particles and polyurethane adhesive.
[0009] The technical solution of the present invention has the following beneficial effects:
[0010] 1. In the ceramic-coated polyolefin diaphragm prepared by the preparation method of the present invention, the surface of the base membrane is divided into two coating layers, wherein the inner layer is a porous epoxy resin with excellent permeability, which serves as a buffer layer between the outer layer mainly composed of ceramic particles and the base membrane, thereby avoiding clogging of the base membrane pores by ceramic particles.
[0011] 2. In the ceramic-coated polyolefin diaphragm prepared by the preparation method of the present invention, the inner layer porous epoxy adhesive serves as a strong adhesive with a low shrinkage rate to connect the outer layer and the base membrane, reducing the influence of shrinkage stress of other resin-type adhesives on the surface of the base membrane; at the same time, the adhesive used in the outer layer is a polyurethane adhesive with the highest shrinkage rate, and the porosity can be further improved after curing and shrinkage.
[0012] 3. In the ceramic-coated polyolefin diaphragm prepared according to the preparation method of the present invention, the inner layer epoxy adhesive has a higher glass transition temperature and greater rigidity, which can slow down the thermal runaway of the diaphragm at high temperatures; while the ceramic particles bonded by polyurethane in the outer layer have better elasticity, making the ceramic coating more flexible. DETAILED DESCRIPTION
[0013] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the specific implementation of the present invention is further described below. Obviously, the embodiments described therein are only part of the implementation of the present invention, which is an explanation of the technical solution of the present invention rather than a limitation.
[0014] A method for preparing a ceramic-coated polyolefin diaphragm of the present invention comprises the following steps:
[0015] The inner layer slurry is uniformly coated on at least one surface of the polyolefin base film, and a first coating layer is formed after solidification, cleaning and drying; the outer layer slurry is uniformly coated on the surface of the first coating layer, and a second coating layer is formed after solidification to obtain the ceramic coated polyolefin diaphragm. The inner layer slurry includes a porous epoxy adhesive, and the outer layer slurry includes inorganic ceramic particles and a polyurethane adhesive.
[0016] Furthermore, the porous epoxy adhesive comprises the following components in parts by weight: 10 parts of epoxy resin, 15-25 parts of porogen, 2-4 parts of curing agent and 0.5-1 part of cellulose ether.
[0017] Cellulose ether is rich in hydroxyl groups and has strong adhesiveness. It can also participate in and promote the curing of epoxy resin, improve the thermal stability of the cured product, and reduce the brittleness of the epoxy resin without affecting its rigidity. In other words, cellulose ether is used as an auxiliary binder, curing accelerator and stabilizer of the epoxy adhesive. The cellulose ether is preferably sodium carboxymethyl cellulose (CMC).
[0018] Preferably, the epoxy resin is a bisphenol epoxy resin, the porogen is water or polyethylene glycol with a molecular weight between 100 and 600, and the curing agent is an amine curing agent. More preferably, the epoxy resin is bisphenol A epoxy resin E-51, the porogen is PEG-400, and the curing agent is a mixture of aromatic amine DDS and polyether amine D230 in a mass ratio of 2:1 to 3:1; correspondingly, the porous epoxy adhesive also includes a promoter such as 1phr of boron trifluoride-monoethylamine complex.
[0019] Furthermore, the inner layer slurry also includes a thermally conductive ceramic material, the mass fraction of the thermally conductive ceramic material in the inner layer slurry is 8-12%, and the remainder is the porous epoxy resin.
[0020] After curing and removing the porogen, the mass fraction of the thermally conductive ceramic material in the solids is about 30-50% of the solids, which is less than half of the content of the inorganic ceramic particles in the outer layer, playing the role of reinforcing the inner layer and avoiding heat accumulation. The inner layer thermally conductive ceramic material can be selected from corresponding ceramic particles or other forms such as ceramic fibers, and its size is smaller than the thickness of the first coating layer.
[0021] Preferably, the thermally conductive ceramic material is at least one of silicon carbide, silicon nitride, aluminum nitride and beryllium oxide. The thermal conductivity of the ceramic material is above 100 W / (m·K) and the mechanical strength is extremely high.
[0022] Furthermore, the inorganic ceramic particles are boehmite or alumina. Compared with the above thermal conductive ceramic materials, boehmite and high-purity alumina have lower density and hardness, better electromagnetic properties and lower price.
[0023] Preferably, the D50 particle size of the inorganic ceramic particles is 0.2-0.5 μm. Since the inorganic ceramic particles do not directly contact the base film and do not block the pores of the diaphragm, the particle size of the ceramic particles can be smaller to enhance their bonding.
[0024] Furthermore, the mass fraction of inorganic ceramic particles in the outer layer slurry is 30-60%, the mass fraction of polyurethane adhesive is 1-4%, the outer layer slurry also includes a mass fraction of 0.5-2% dispersant, and the balance is water. The dispersant is preferably a composite of polyethylene glycol (PEG) and sodium dodecyl sulfate (SDS).
[0025] The polyurethane adhesive can be any one with a higher shrinkage rate in the prior art, preferably a two-component polyurethane adhesive consisting of a main agent (component A) and a curing agent (component B).
[0026] Furthermore, the thickness of the first coating layer is 0.5-1.2 μm, and the thickness of the second coating layer is 2-3.5 μm. The first coating layer only plays a role of blocking and buffering, and its thickness is lower than that of the second coating layer.
[0027] Furthermore, the polyolefin base film is made of high-density polyethylene and / or polypropylene, and has a thickness of 6 to 12 μm. In the case of the epoxy resin of the first coating layer as a reinforcing support, a base film with a relatively low thickness can be selected to enhance the compactness of the lithium battery.
[0028] The present invention is described in detail below with reference to the embodiments. The experimental methods are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified; the order of the described implementation steps does not strictly represent the order of specific implementation, except for those with logical associations.
[0029] Example 1
[0030] Preparation of inner layer slurry:
[0031] 1 kg of Nan Ya epoxy resin 128 (E-51), 2.2 kg of water, 0.2 kg of diaminodiphenyl sulfone (DDS), 0.1 kg of polyetheramine D230, 0.07 kg of sodium carboxymethyl cellulose (CMC) and 0.01 kg of boron trifluoride-monoethylamine complex were mixed evenly and degassed to obtain an inner layer slurry.
[0032] Preparation of outer layer slurry:
[0033] 5 kg of high-purity alumina (D50 particle size 0.5 μm) was mixed with 4.5 kg of water, and then 0.3 kg of component A and 0.06 kg of component B of a two-component polyurethane adhesive (Henkel Pattex R710) were added and mixed evenly to obtain an outer layer slurry.
[0034] Preparation of ceramic coated polyolefin separator:
[0035] A high-density polyethylene base film (thickness 8 μm, porosity 40%, softening point>125°C) was prepared, the obtained inner layer slurry was evenly coated on one side of the base film, cured at 80°C for 0.5h, then cured at 100°C for 1h, and finally cured at 120°C for 2h, the obtained coating film was ultrasonically soaked in water for 30min, and a 1 μm thick first coating layer was formed after drying. The obtained outer layer slurry was evenly coated on the surface of the first coating layer, and a 2.5 μm thick second coating layer was formed after curing to obtain the ceramic-coated polyolefin separator.
[0036] Example 2
[0037] The method for preparing the ceramic-coated polyolefin diaphragm in this embodiment is exactly the same as that in Example 1, and the steps for preparing the inner layer slurry are as follows:
[0038] 1kg Nan Ya epoxy resin 128 (E-51), 2kg PEG-400, 0.25kg diaminodiphenyl sulfone (DDS), 0.1kg polyetheramine D230, 0.1kg sodium carboxymethyl cellulose (CMC) and 0.01kg boron trifluoride-monoethylamine complex were mixed, and finally 0.38kg silicon carbide fiber (average length 100nm) was added and stirred evenly, and degassing treatment was performed to obtain an inner layer slurry.
[0039] Example 3
[0040] The method for preparing the ceramic-coated polyolefin diaphragm in this embodiment is exactly the same as that in Example 1, and the steps for preparing the outer layer slurry are as follows:
[0041] 4 kg of boehmite (D50 particle size 0.3 μm) was mixed with 5.5 kg of water, and then 0.25 kg of component A and 0.05 kg of component B of a two-component polyurethane adhesive (UZIN KR430 sh) were added and mixed, and finally 0.1 kg of PEG-1000 and 0.05 kg of SDS were added and stirred evenly to obtain an outer layer slurry.
[0042] Example 4
[0043] The method for preparing the ceramic-coated polyolefin diaphragm and the inner layer slurry in this embodiment is exactly the same as that in Embodiment 2, and the method for preparing the outer layer slurry is exactly the same as that in Embodiment 3.
[0044] Example 5
[0045] The method for preparing the inner layer slurry and the outer layer slurry in this embodiment is exactly the same as that in embodiment 4. The steps for preparing the coated polyolefin diaphragm are as follows:
[0046] A polypropylene base film (thickness 12 μm, porosity 39%) was prepared, the obtained inner layer slurry was evenly coated on both sides of the base film, cured at 80°C for 2 hours, and then cured at 130°C for 1.5 hours, the obtained coating film was ultrasonically soaked in water for 30 minutes, and a 0.8 μm thick first coating layer was formed after drying. The obtained outer layer slurry was evenly coated on the surface of the first coating layer, and a 2 μm thick second coating layer was formed after curing to obtain the ceramic coated polyolefin separator.
[0047] Comparative Example 1
[0048] The only difference between this comparative example and Example 1 is that there is no first coating layer, and the obtained outer layer slurry is directly and evenly coated on the surface of one side of the base film to form a coating layer with a thickness of 4 μm after curing.
[0049] Comparative Example 2
[0050] The only difference between this comparative example and Example 1 is that the porous epoxy adhesive is replaced by a common epoxy adhesive, that is, the porogen PEG-400 is not added to the formula.
[0051] The ceramic-coated polyolefin diaphragms obtained in the above embodiments and comparative examples are tested below.
[0052] 1. Membrane permeability test
[0053] The thickness and uniformity of the ceramic-coated polyolefin separator were measured using a CHY-CU thickness gauge, the porosity was measured using a liquid absorption method, and the air permeability was measured using an air permeability tester. The test results are shown in Table 1.
[0054] Table 1 Thickness and deviation, porosity and permeability of the diaphragm
[0055] Group Thickness(μm) Maximum deviation (μm) Porosity (%) Air permeability (s / 100mL) Example 1 11.6 0.4 42 83 Example 2 12.0 0.2 40 90 Example 3 11.5 0.3 43 81 Example 4 11.8 0.1 41 89 Example 5 17.8 0.2 40 184 Comparative Example 1 11.7 1.1 40 127 Comparative Example 2 11.4 0.1 35 314
[0056] The test is carried out in accordance with the requirements of national standard GB / T36363-2018.
[0057] 2. Bond strength and thermal performance test
[0058] Heating at 130℃ for 1h, testing the thermal shrinkage rate (maximum value in each direction) of the ceramic coated polyolefin separator; increasing the temperature to test the thermal film breaking temperature, and observing whether the ceramic falls off before reaching the film breaking temperature, and scoring according to the adhesion level. The test results are shown in Table 2.
[0059] Table 2 Thermal shrinkage rate, thermal film breaking temperature and ceramic particle adhesion level of the diaphragm
[0060] Group Thermal shrinkage (%) Thermal film breaking temperature (℃) Adhesion grade Example 1 1.4 187 1 Example 2 1.1 192 1 Example 3 1.4 188 1 Example 4 1.0 192 1 Example 5 1.8 198 1 Comparative Example 1 3.6 166 3 Comparative Example 2 0.9 194 1
[0061] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description, and the obvious changes or modifications derived therefrom should still be considered as the protection scope of the present invention.
Claims
1. A method for preparing a ceramic-coated polyolefin diaphragm, characterized in that: The steps include: The inner layer slurry is uniformly coated on at least one surface of the polyolefin base film, and a first coating layer is formed after solidification, cleaning and drying; the outer layer slurry is uniformly coated on the surface of the first coating layer, and a second coating layer is formed after solidification to obtain the ceramic coated polyolefin diaphragm; The inner layer slurry includes porous epoxy adhesive, and the outer layer slurry includes inorganic ceramic particles and polyurethane adhesive.
2. The method for preparing a ceramic-coated polyolefin diaphragm according to claim 1, characterized in that: The porous epoxy adhesive comprises the following components in parts by weight: 10 parts of epoxy resin, 15-25 parts of porogen, 2-4 parts of curing agent and 0.5-1 part of cellulose ether.
3. The method for preparing a ceramic-coated polyolefin diaphragm according to claim 2, characterized in that: The epoxy resin is a bisphenol epoxy resin, the porogen is water or polyethylene glycol with a molecular weight between 100 and 600, and the curing agent is an amine curing agent.
4. The method for preparing a ceramic-coated polyolefin diaphragm according to any one of claims 1 to 3, characterized in that: The inner layer slurry also includes a thermally conductive ceramic material. The mass fraction of the thermally conductive ceramic material in the inner layer slurry is 5-8%, and the remainder is the porous epoxy adhesive.
5. The method for preparing a ceramic-coated polyolefin diaphragm according to claim 4, characterized in that: The thermally conductive ceramic material is at least one of silicon carbide, silicon nitride, aluminum nitride and beryllium oxide.
6. The method for preparing a ceramic-coated polyolefin diaphragm according to claim 1, characterized in that: The inorganic ceramic particles are boehmite or alumina.
7. The method for preparing a ceramic-coated polyolefin diaphragm according to claim 6, characterized in that: The D50 particle size of the inorganic ceramic particles is 0.2-0.5 μm.
8. The method for preparing a ceramic-coated polyolefin diaphragm according to any one of claims 1, 6 and 7, characterized in that: The mass fraction of inorganic ceramic particles in the outer layer slurry is 30-60%, the mass fraction of polyurethane adhesive is 1-4%, the outer layer slurry also includes a dispersant with a mass fraction of 0.5-2%, and the balance is water.
9. The method for preparing a ceramic-coated polyolefin diaphragm according to claim 1, characterized in that: The thickness of the first coating layer is 0.5-1.2 μm, and the thickness of the second coating layer is 2-3.5 μm.
10. The method for preparing a ceramic-coated polyolefin diaphragm according to claim 1, characterized in that: The material of the polyolefin-based film is high-density polyethylene and / or polypropylene, and the thickness of the polyolefin-based film is 6-12 μm.